2019
DOI: 10.1016/j.celrep.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Hematopoietic Oxidase NOX2 Regulates Self-Renewal of Leukemic Stem Cells

Abstract: SUMMARY The NADPH-dependent oxidase NOX2 is an important effector of immune cell function, and its activity has been linked to oncogenic signaling. Here, we describe a role for NOX2 in leukemia-initiating stem cell populations (LSCs). In a murine model of leukemia, suppression of NOX2 impaired core metabolism, attenuated disease development, and depleted functionally defined LSCs. Transcriptional analysis of purified LSCs revealed that deficiency of NOX2 collapses the self-renewal program and activates inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 54 publications
3
81
0
5
Order By: Relevance
“…High reactive oxygen species (ROS) levels in bulk CML and AML cells, compared to normal haematopoietic cells, are often explained through the actions of oncogenic kinases like BCR-ABL1, FLT3 or KRAS, which increase the activities of RAC GTPases, 67,68 or the actions of of membrane-bound NADPH oxidases, 69,70 which correlate with increased dependence of leukemic cells on mitochondrial respiration 71,72 . However, extremes in ROS levels (too high or too low) present problems to LSCs, as these extremes can promote differentiation and impair stem cell function 69,73 35,[87][88][89] . The exception to this appears to be MLL (also known as KMT2A)-rearranged AML, where LSCs possess similarities to an mRNA signature from embryonic stem cells 40 .…”
Section: [H2] Cell Surface Marker Definitions the Expression Of Cd34mentioning
confidence: 99%
“…High reactive oxygen species (ROS) levels in bulk CML and AML cells, compared to normal haematopoietic cells, are often explained through the actions of oncogenic kinases like BCR-ABL1, FLT3 or KRAS, which increase the activities of RAC GTPases, 67,68 or the actions of of membrane-bound NADPH oxidases, 69,70 which correlate with increased dependence of leukemic cells on mitochondrial respiration 71,72 . However, extremes in ROS levels (too high or too low) present problems to LSCs, as these extremes can promote differentiation and impair stem cell function 69,73 35,[87][88][89] . The exception to this appears to be MLL (also known as KMT2A)-rearranged AML, where LSCs possess similarities to an mRNA signature from embryonic stem cells 40 .…”
Section: [H2] Cell Surface Marker Definitions the Expression Of Cd34mentioning
confidence: 99%
“…Enrichment of oxidative phosphorylation pathway ( Fig.2A) Research. and increasing cycling of liver leukemia cells may result in an increased ROS level (33).…”
Section: Endogenous Lipg Is Critical For Proliferation and Chemo-resimentioning
confidence: 99%
“…In fact, AML proliferation is accompanied by NOX2-dependent extracellular ROS production in more than 60% of AML patients [ 10 ]. Studies have shown that fms-like tyrosine kinase 3—internal tandem repeat (FLT3-ITD) signaling involved NOX4 activity [ 15 ], while others demonstrated that NOX2 is implicated in leukemic development [ 11 , 16 , 17 , 18 ]. In addition, NOX-dependent ROS production has been shown to trigger mitochondrial transfer from BM stromal cells to AML blasts, thus fueling AML proliferation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%